HERPES ZOSTER DEXTRA FACIAL - Panonsih, Resati Nando; Valentine, Amelia; Rizdanti, Fezagustia; Rachmawati, Endah; Risdinar, Risa Rismaya; Imalambasi, Nada Nisrina; Faatin, Nafiisa Nur; Prayoga, Muhammad Fachmi; Ningrum, Dewi Wahyu Setia; Fitriani, Anisa (Medula, 2024)
Herpes zoster is a manifestation of reactivation of latent endogenous infection of the varicella zoster virus in the neurons of the dorsal root sensory ganglion, cranial nerve ganglion or autonomic nerve ganglion which spreads to nerve tissue and skin in the same segment. Herpes zoster occurs sporadically throughout the year without knowing the season. The incidence of herpes zoster reaches two to three cases per thousand population each year. The incidence and severity of the disease increases with age. More than half of all cases reported occur in people over 60 years of age and complications occur in almost 50% of people in old age. Herpes zoster is rarely found at an early age (children and young adults), but when it occurs, it is likely due to maternal varicella during pregnancy. The incidence of herpes zoster in men and women is the same. The risk of disease increases with the presence of malignancy, or with bone marrow/kidney transplantation or HIV infection. There is no gender predilection. Herpes zoster is contagious but its transmission capacity is small compared to varicella. The treatment received by the patient was observing bleeding, checking vital signs periodically, and providing pharmacological treatment in the form of acyclovir 400mg tablets and acyclovir cream. Patients are advised to check in a week later. The prognosis for this patient is dubia ad bonam.